2007
DOI: 10.1007/s10611-007-9055-7
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the implementation of laws with regard to female genital mutilation in Europe

Abstract: This paper presents results of a survey on legislation regarding female genital mutilation in 15 European member states, as well as the results of a comparative analysis of the implementation of these laws in Belgium, France, Spain, Sweden and the UK. The research showed that although both criminal laws and child protection laws are implemented a number of difficulties with the implementation of these laws remain. The article suggests that efforts should primarily focus on child protection measures, but also o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 12 publications
1
38
0
Order By: Relevance
“…If we assume that those who were already knowledgeable about FGM participated in the survey, the proportion of those who are not aware of the law on FGM is high. This corroborates the findings of an earlier study on the implementation of the law on FGM in Belgium, which revealed that health professionals knew little about FGM, about the criminal law provisions with regard to FGM, and, in particular, about the procedures, which should be implemented in the event of confrontation with a victim of FGM 6,7 . It also showed that attitudes of health professionals, such as the fear of being labelled a racist or the respect for other cultures, might interfere with the effective application of the law.…”
Section: Training Guidelines and Legal Provisions With Regard To Fgmsupporting
confidence: 89%
See 2 more Smart Citations
“…If we assume that those who were already knowledgeable about FGM participated in the survey, the proportion of those who are not aware of the law on FGM is high. This corroborates the findings of an earlier study on the implementation of the law on FGM in Belgium, which revealed that health professionals knew little about FGM, about the criminal law provisions with regard to FGM, and, in particular, about the procedures, which should be implemented in the event of confrontation with a victim of FGM 6,7 . It also showed that attitudes of health professionals, such as the fear of being labelled a racist or the respect for other cultures, might interfere with the effective application of the law.…”
Section: Training Guidelines and Legal Provisions With Regard To Fgmsupporting
confidence: 89%
“…Most of these women and girls were from Ghana and the Democratic Republic of Congo (former Zaire). Estimations based on such extrapolations should be interpreted with caution 6 . It should also be noted that the persons concerned represent only a small sub-group of the Belgian and foreign populations, as most non-European immigrants are from Morocco and Turkey where FGM is not practised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On 20 December 2012, the UN General Assembly adopted a first-ever resolution against FGC, defining it as "an irreparable, irreversible abuse that impacts negatively on the human rights of women and girls" and reaffirmed "that female genital mutilations are a harmful practice that constitutes a serious threat to the health of women and girls […] and that the abandonment of this harmful practice can be achieved as a result of a comprehensive movement that involves all public and private stakeholders in society" (UN General Assembly, 2012: 2) (Tostan, 1999;Unicef-IRC, 2010). In most African countries penalties range from a minimum of three months to a maximum of life in prison and many impose monetary fines (Leye et al, 2007;WHO, 2008).…”
Section: Female Genital Cutting: Definition and Diffusionmentioning
confidence: 99%
“…In Western countries, legislation has been instituted as the main intervention tool (European Parliament 2004;Leye et al 2007;UNICEF 2005;WHO 2006). Efforts to abandon the practice of FGM/C in Africa have used several different approaches, including those based on legal mechanisms, human rights frameworks, health risks, alternative rites and comprehensive social development approaches (Muteshi and Sass 2005).…”
Section: Introductionmentioning
confidence: 99%